2018
DOI: 10.1016/j.solmat.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Design of high-temperature solar-selective coatings based on aluminium titanium oxynitrides AlyTi1-y(OxN1-x). Part 2: Experimental validation and durability tests at high temperature

Abstract: The durability of two solar-selective aluminium titanium oxynitride multilayer coatings was studied under conditions simulating realistic operation of central receiver power plants. The coatings were deposited by cathodic vacuum arc applying an optimized design concept for complete solar-selective coating (SSC) stacks. Compositional, structural and optical characterization of initial and final stacks was performed by scanning electron microscopy, elastic recoil detection, UV-Vis-NIR-IR spectrophotometry and X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…For CrN1.08, the n value increases continuously from n=2.16 at 350 nm to a maximum of 3.38 at ≈1800 nm, reaching a steady-state. The extinction coefficient "k" increases from 0.85 at 350 nm to 1.27 at 1100 nm, and then decreases with the wavelength until 0.54, characteristic of a semiconductor behavior [18,26]. The optical constants match with the trend reported in the literature for a CrN reference [26], although smaller values of n and k are obtained in the whole energy range.…”
Section: Crny Films: Optical Characterizationsupporting
confidence: 81%
See 1 more Smart Citation
“…For CrN1.08, the n value increases continuously from n=2.16 at 350 nm to a maximum of 3.38 at ≈1800 nm, reaching a steady-state. The extinction coefficient "k" increases from 0.85 at 350 nm to 1.27 at 1100 nm, and then decreases with the wavelength until 0.54, characteristic of a semiconductor behavior [18,26]. The optical constants match with the trend reported in the literature for a CrN reference [26], although smaller values of n and k are obtained in the whole energy range.…”
Section: Crny Films: Optical Characterizationsupporting
confidence: 81%
“…metallic to covalent), resulting in the variation of the optical properties and electrical resistivity [7,8,[10][11][12][13], as well as improving their mechanical properties and oxidation resistance [14]. In this context, it has been reported that materials as TiNOx (commercially available for mid-temperature SSC [5]) and others materials as TiAlN, TiAlNO, TiAlSiN or NbAlN, display low reflectance and high absorption coefficient in the UV-Vis spectral range, making them excellent candidates to be used as components in mid-and high-temperature SSC [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, two Al y Ti 1-y (O x N 1-x ) thin film samples were analyzed. They are named #1 and #5 according to the notation used in previous works (see Table 2) [27,28]. Samples were grown using only reactive gases (N 2 and O 2 ) without Ar gas assistance.…”
Section: Thin Film Growthmentioning
confidence: 99%
“…The reported work assessed the need of a comprehensive understanding of the chemical bonding and thin film composition in order to properly adjust the final solar selectivity of the stack. The durability of selected multilayers was studied after (i) asymmetric tests of 12 h at 450, 650, and 800 °C and (ii) 900 h of heating-cooling thermal cycles between 300 and 600 °C in air [28]. The designed SSC fulfilled the performance criterion for high-temperature SCC after the long-term thermal cycling between 300 and 600 °C in air.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26,27 ] The SSAs based on AlyTi 1− y (O x N 1− x ) films using cathodic vacuum arc (CVA) successfully withstood breakdown at 650 °C for 12 h in air. [ 28 ] A novel SSA based on a MoSi 2 −Si 3 N 4 hybrid composite with a Al 2 O 3 capping layer showed exceptional long‐term stability at 600 °C in air. [ 29 ] However, diffusion and oxidation are inevitable in open air atmosphere at high temperature, thus resulting in deterioration in the optical properties of the coatings.…”
Section: Introductionmentioning
confidence: 99%